Short- and long-term protective efficacy against clade 2.3.4.4 H5N2 highly pathogenic avian influenza virus following prime-boost vaccination in turkeys. Issue 42 (9th October 2017) - Santos, Jefferson J.S.; Obadan, Adebimpe O.; Garcia, Stivalis Cardenas; Carnaccini, Silvia; Kapczynski, Darrell R.; Pantin-Jackwood, Mary; Suarez, David L.; Perez, Daniel R.
Highlights: A prime-boost vaccine strategy protects turkeys against a clade 2.3.4.4 H5N2 HPAIV. A recombinant alphavirus replicon produced protective responses. An adjuvanted-inactivated influenza virus vaccine produced protection. HI titers were discernible by 3 weeks post-boost. HI titers were drastically reduced by 13 weeks post-boost. Best overall protective responses were achieved by alternating vaccine strategies. Abstract: Highly pathogenic avian influenza virus (HPAIV) infections are frequently associated with systemic disease and high mortality in domestic poultry, particularly in chickens and turkeys. Clade 2.3.4.4 represents a genetic cluster within the Asian HPAIV H5 Goose/Guangdong lineage that has transmitted through migratory birds and spread throughout the world. In 2014, clade 2.3.4.4 strains entered the U.S. via the Pacific flyway, reassorted with local strains of the North American lineage, and produced novel HPAIV strains of the H5N1, H5N2, and H5N8 subtypes. By 2015, the H5N2 HPAIVs disseminated eastwards within the continental U.S. and Canada and infected commercial poultry, causing the largest animal health outbreak in recent history in the U.S. The outbreak was controlled by traditional mass depopulation methods, but the outbreak was of such magnitude that it led to the consideration of alternative control measures, including vaccination. In this regard, little information is available on the long-term protection of turkeys vaccinated against avian influenza. In this report, a vaccination study was carried out in turkeys using 3 prime-boost approaches with a combination of 2 different vaccines, an alphavirus-based replicon vaccine and an adjuvanted-inactivated reverse genetics vaccine. Vaccine efficacy was assessed at 6 and 16 weeks of age following challenge with a prototypic novel clade 2.3.4.4 H5N2 HPAIV. All three vaccines protocols were protective with significantly reduced virus shedding and mortality after challenge at 6 weeks of age. In contrast, significant variations were seen in 16-week old turkeys after challenge: priming with the alphavirus-based replicon followed by boost with the adjuvanted-inactivated vaccine conferred the best protection, whereas the alphavirus-based replicon vaccine given twice provided the least protection. Our study highlights the importance of studying not only different vaccine platforms but also vaccination strategies to maximize protection against HPAIV especially with regards to the longevity of vaccine-induced immune response.